Pelatihan Menulis Karya Sastra Puisi di SMA 13 Makassar - Abidin, Aslan; Ridwan; Filawati (Jurusan Pendidikan Teknik Elektro, 2024)
Reading and writing skills are one of the most important language skills needed by students. Good reading habits will develop self-awareness to explore language, enrich vocabulary, seek inspiration and encourage students' creative thinking when writing literary works, especially poetry. Therefore, creative strategies are needed to increase students' potential and interest, including training writing skills, especially writing literary works. This partnership program is implemented in the form of poetry writing training at SMA 13 Makassar. 13 Makassar. This training aims to increase students' knowledge and skills in writing poetry. This activity is in line with the Tri Dharma of Higher Education which provides learning experiences for students through the practice of literary writing skills. literary writing skills. The method used in this activity is by practicing writing poetry based on topics that are interesting to children. The objectives to be achieved from this PKM activity are as follows: (1) to motivate students about the importance of gaining aesthetic and intellectual knowledge through reading literary works; (2) students gain knowledge (theoretical) about good writing techniques so that students are able to communicate their ideas in the form of poetry. communicate their ideas in the form of poetry; (3) create a poetic climate that can make students enjoy reading and writing poetry; (4) improve the intellectual quality of students by continuing to share knowledge and provide adequate training on the basics of writing poetry. the basics of writing good poetry; and (5) publishing an anthology of students' poetry to give students pride. anthology of students' poetry to provide intellectual pride for having creating and publishing poetry artworks.